The natural theology of evolution - Shearman, J. N., author.
1 online resource.
Keywords: Originally published in 1915, The Natural Theology of Evolution looks at the concept of natural theology, examining the argument for the existence of God based on reason and ordinary experiences of nature. The book looks at natural theology in light of Darwin's theory of evolution, and how this important discovery affected belief in intelligent design. The book argues that the discovery of evolution, far from diminishing the existence of God, provides stronger proof for an intelligently designed earth and therefore the existence of God. This book provides a unique and interesting take on the debates surrounding evolution in the late 19th and early 20th century. It will be of interest to philosophers, historians of religion and natural historians alike.